PENATAUSAHAAN KEUANGAN DALAM IMPLEMENTASI KEBIJAKAN WORK FROM HOME STASIUN TELEVISI REPUBLIK INDONESIA (TVRI) BALI - Tantira, Seligia Ayu; Pratiwi, Nuning Indah (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
Financial administration during the Work From Home (WHF) policy at Stasiun Televisi Republik Indonesia (TVRI) Bali has undergone changes, particularly in the recording, verification, and reporting processes, which must be carried out remotely. The Work From Home (WFH) implementation has presented challenges such as limited work equipment, internet disruptions, difficulties in document verification, and differences in employee technology skills. Financial management processes can continue through adjustments such as the use of digital documents, electronic contract signatures, and virtual coordination. Financial administration continues during Work From Home (WHF), but requires strengthening digital systems and improving employee competencies to optimize accountability and work effectiveness.